Mengembangkan Keterampilan Motorik Halus Anak Melalui Kegiatan 3 M - Sri Ayu Laali (Universitas Lampung, 2019)
The purpose of this study was to describe the development of fine motor skills through 3 M activities (coloring, cutting and sticking) on students in the B2 kindergarten group Al-Ittihad. This study is a Classroom Action Research (CAR). The procedure for implementing classroom action research consists of two cycles. Each cycle is carried out in accordance with the changes to be achieved as what has been designed in the factors to be investigated. The subjects in this study were as many as 20 people consisting of 10 male children and 10 female students in Musdalifah Poasia Kindergarten 2010/2011 Academic Year. From the results of the evaluation of observations, it can be concluded that through 3M activities (coloring, cutting and sticking) that are carried out optimally can develop the fine motoric abilities of students in the kindergarten Al-Ittihad B2 group. Recommendations for further research in order to re-raise the same problems but with other methods, techniques and strategies as well as different actions in order to provide input or new findings in optimally developing the potential of students in kindergartenKeywords: Fine motor skills, early childhood, activities (coloring, cutting and sticking)DOI: http://dx.doi.org/10.23960/jiip.v1i2.18028